Standing the test of COVID-19: charting the new frontiers of medicine - Cauchemez, Simon; Cossu, Giulio; Delzenne, Nathalie; Elinav, Eran; Fassin, Didier; Fischer, Alain; Hartung, Thomas; Kalra, Dipak; Netea, Mihai; Neyts, Johan; Rappuoli, Rino; Pizza, Mariagrazia; et al. (Frontiers in Science, 2024)
The COVID-19 pandemic accelerated research and innovation across numerous fields of medicine. It emphasized how disease concepts must reflect dynamic and heterogenous interrelationships between physical characteristics, genetics, co-morbidities, environmental exposures, and socioeconomic determinants of health throughout life. This article explores how scientists and other stakeholders must collaborate in novel, interdisciplinary ways at these new frontiers of medicine, focusing on communicable diseases, precision/personalized medicine, systems medicine, and data science. The pandemic highlighted the critical protective role of vaccines against current and emerging threats. Radical efficiency gains in vaccine development (though mRNA technologies, public and private investment, and regulatory measures) must be leveraged in future, together with continued innovation in monoclonal antibodies, novel antimicrobials, and multisectoral, international action against communicable diseases. Inter-individual heterogeneity in the pathophysiology of COVID-19 prompted the development of targeted therapeutics. Beyond COVID-19, medicine will be increasingly personalized via advanced omics-based technologies and systems biology—for example targeting the role of the gut microbiome and specific mechanisms underlying immunoinflammatory diseases and genetic conditions. Modelling proved critical to strengthen risk assessment and support COVID-19 decision-making. Advanced computational analytics and artificial intelligence (AI) may help integrate epidemic modeling, clinical features, genomics, immune factors, microbiome data, and other anthropometric measures into a “systems medicine” approach. The pandemic also accelerated digital medicine, giving telehealth and digital therapeutics critical roles in health systems resilience and patient care. New research methods employed during COVID-19, including decentralized trials, could benefit evidence-generation and decision making more widely. In conclusion, [...]